Current use of medical eponyms – a need for global uniformity in scientific publications - Arora Nalini; Barik Sukumar; Jana Narayan (BMC Medical Research Methodology, 2009)
Abstract Background Although eponyms are widely used in medicine, they arbitrarily alternate between the possessive and nonpossessive forms. As very little is known regarding extent and distribution of this variation, the present study was planned to assess current use of eponymous term taking "Down syndrome" and "Down's syndrome" as an example. Methods This study was carried out in two phases – first phase in 1998 and second phase in 2008. In the first phase, we manually searched the terms "Down syndrome" and "Down's syndrome" in the indexes of 70 medical books, and 46 medical journals. In second phase, we performed PubMed search with both the terms, followed by text-word search for the same. Results In the first phase, there was an overall tilt towards possessive form – 62(53.4%) "Down's syndrome" versus 54(46.6%) "Down syndrome." However, the American publications preferred the nonpossesive form when compared with their European counterpart (40/50 versus 14/66; P < 0.001). In the second phase, PubMed search showed, compared to "Down syndrome," term "Down's syndrome" yielded approximately 5% more articles. The text-word search of both forms between January 1970 and June 2008 showed a gradual shift from "Down's syndrome" to "Down syndrome," and over the last 20 years, the frequency of the former was approximately halved (33.7% versus 16.5%; P < 0.001). The abstracts having possessive form were mostly published from the European countries, while most American publications used nonpossesive form consistently. Conclusion Inconsistency in the use of medical eponyms remains a major problem in literature search. Because of linguistic simplicity and technical advantages, the nonpossessive form should be used uniformly worldwide.